Cruel to Be Kind: Factors Underlying Altruistic Efforts to Worsen Another Person's Mood. (July 2017) - López-Pérez, Belén; Howells, Laura; Gummerum, Michaela
When aiming to improve another person's long-term well-being, people may choose to induce a negative emotion in that person in the short term. We labeled this form of agent-target interpersonal emotion regulation altruistic affect worsening and hypothesized that it may happen when three conditions are met: (a) The agent experiences empathic concern for the target of the affect-worsening process, (b) the negative emotion to be induced helps the target achieve a goal (e.g., anger for confrontation or fear for avoidance), and (c) there is no benefit for the agent. This hypothesis was tested by manipulating perspective-taking instructions and the goal to be achieved while participants ( N = 140) played a computer-based video game. Participants following other-oriented perspective-taking instructions, compared with those following objective perspective-taking instructions, decided to induce more anger in a supposed fellow participant who was working to achieve a confrontation goal and to induce more fear in a supposed fellow participant who was working to achieve an avoidance goal.